Persistent differences in patterns of brain activation after sports- related concussion: a longitudinal fMRI study - Dettwiler, Annegret; Murugavel, Murali; Putukian, Margot; Echemendia, Ruben; Cubon, Valerie; Furtado, John; Osherson, Daniel (British journal of sports medicine, 2013)
Objective To define neural correlates of SRC during the 2 month post-injury period using a working memory (WM) task and fMRI and correlate these to clinical measures. Design Longitudinal fMRI study assessing subject's brain activation as they perform a N-back task (N=1 to 3) consisting of 30 randomised blocks. Setting Varsity collegiate athletes were recruited from high-risk sports teams. Images were acquired on a 3T Siemens Skyra scanner. Subjects All athletes were evaluated prospectively within 48 h, 2, 8 weeks postinjury on SCAT2 and hybrid NP battery (ImPACT, paper and pencil tests). 15 right-handed, varsity contact sport athletes who sustained a SRC were scanned at 72 h, 2 and 8 weeks post injury. 15 uninjured control athletes were scanned at baseline and 2 weeks. Outcome Measures Post-hoc, whole brain t tests of the 2–1 contrast were performed using FSL-FEAT (mixed effects modelling, z>2.3, corrected p=0.05). Results Across all 3 sessions, concussed athletes demonstrated significantly increased activation in the right dorsolateral prefrontal cortex (DLPFC). In session 1, concussed subjects demonstrated increased activation in additional areas: left DLPFC and bilateral inferior parietal. In all 3 sessions, no significant between group differences were observed in subjects performance for all 3 N-back task conditions. Conclusions Functional brain activation differences persist at 8 weeks post injury in concussed athletes, despite the fact that their performance on a WM task is comparable to normal controls and normalisation of clinical/hybrid NP tests. These results might indicate a delay between neural and behaviorally-assessed recovery. Acknowledgements This research was supported by NJBIR Grant 10-3217-BIR-E-0 AMSSM Grant 005548 Goldstein Family Fund.